1992
DOI: 10.1002/pola.1992.080301019
|View full text |Cite
|
Sign up to set email alerts
|

Para‐Xylylenes and analogues by base‐induced elimination from 1,4‐bis‐(dialkylsulfoniomethyl)arene salts in poly(1,4‐arylene vinylene) synthesis by the wessling soluble precursor method

Abstract: para‐Xylylenes are generated by treatment of various 1,4‐bis(dialkylsulfoniomethyl)arene dihalides with base in water, methanol, and aqueous acetonitrile, as shown by UV‐Vis spectroscopy. This procedure allows the monitoring of the transient xylylene monomers that yield polyelectrolyte precursor polymers for poly(arylene vinylene)s, formed by variations of the chemistry developed originally by Wessling and co‐workers. Alkoxy, alkyl, and halogen ring substituents on the sulfonium salt precursors do not greatly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…Wessling postulated a radical mechanism, possibly initiated by dimeric diradicals VI (Scheme 2). [26] In contrast, Lahti et al, [113] Garay and Lenz, [114] and Hsieh [115] reported results that pointed toward anionic chain growth, while Hall and co-workers [116] and, later, Lahti and co-workers [117,118] realized that polymerization also proceeds in acidic media but is suppressed when 2,2,6,6-tetramethylpiperidine-N-oxyl (TEMPO) is added as a scavenger. Also Cho et al, who first favored anionic chain growth, [119] revised his earlier standpoint and has favored radical chain growth since then.…”
Section: The Wessling Routementioning
confidence: 86%
“…Wessling postulated a radical mechanism, possibly initiated by dimeric diradicals VI (Scheme 2). [26] In contrast, Lahti et al, [113] Garay and Lenz, [114] and Hsieh [115] reported results that pointed toward anionic chain growth, while Hall and co-workers [116] and, later, Lahti and co-workers [117,118] realized that polymerization also proceeds in acidic media but is suppressed when 2,2,6,6-tetramethylpiperidine-N-oxyl (TEMPO) is added as a scavenger. Also Cho et al, who first favored anionic chain growth, [119] revised his earlier standpoint and has favored radical chain growth since then.…”
Section: The Wessling Routementioning
confidence: 86%
“…Also, satisfying purity of the products is a challenging issue. Chain‐growth processes on the other hand, such as Wessling, sulfinyl, xanthate and Gilch reactions, give high‐molecular‐weight products, but the chains contain characteristic defects . Impurities, constitutional defects and insufficient molar masses are not tolerable, however, as they downgrade device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, a number of methodologies have been developed to overcome this significant drawback. Most common and effective strategies were the synthesis of soluble precursors that form a conductive coating upon heat treatment [6] and the introduction of alkyl side chains [7] in the polymer structures. It has clearly been demonstrated that alkyl side chains not only enhance the ease of processing, but also modify the electronic properties of the conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%